Optimization of Rumen Microbial Protein Synthesis by Addition of Gambier Leaf Residue to Cattle Feed Supplement - Ramaiyulis; Ningrat, Rusmana Wijaya Setia; Zain, Mardiati; Warly, Lili (Pakistan Journal of Nutrition, 2018)
Background and Objective: This study aimed to achieve optimal microbial protein synthesis by adding various levels of gambier leaf residue (GLR) to cattle feed supplement (CFS). Materials and Methods: Gambier (Uncaria gambir Roxb) leaf residue containing 9.96% condensed tannins was added at levels of 0, 2.5, 5.0 and 7.5% (DM) to CFS formula containing 29% crude protein and then tested in vitro rumen digestion. Results: Addition of 5% GLR significantly decreased the rumen protozoan population by 24.43% (p